Effect of caffeine on neonatal splanchnic blood flow. Issue 2 (1st March 1999) - Lane, Andrew J P; Coombs, Robert C; Evans, David H; Levin, Roy J
Abstract : Doppler ultrasound was used to study the effect of the first intravenous dose of caffeine on splanchnic haemodynamics in preterm neonates. Peak systolic velocity in the superior mesenteric artery and coeliac axis was significantly reduced for 6 hours after caffeine infusion.  The effect of this reduction in blood flow to the neonatal gut is not known.